PATTERN OF METEOROLOGICAL DROUGHT DISTRIBUTION IN THE SLAHUNG RIVER BASIN, PONOROGO, USING THE THEORY OF RUN METHOD - Thoif T; Nur Azizah Affandy; Salwa Nabilah; Dwi Kartikasari; Mahendra Andiek Maulana (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2024)
Drought is a natural event that frequently occurs in Indonesia and significantly impacts various sectors, such as agriculture, plantations, and water resources. This study aims to analyze the level of drought in the Slahung sub-River basin using the Theory of Run method. The data used includes 24 years of rainfall data from three rainfall stations: Ngilo-Ilo, Balong, and Slahung, covering the period from 2000 to 2023. The analysis results show that the longest drought duration at Slahung Station occurred in 2012, lasting 18 months, with the largest cumulative drought recorded in 2010 at -1071 mm. The drought distribution map reveals that 2019 was the driest year, while 2023 was the wettest. This study provides valuable insights into water resource management and drought disaster mitigation planning in the Slahung sub-River basin. Future research is recommended to use longer and higher-quality data, as well as comparisons with other drought analysis methods to improve the accuracy of the analysis.